The Zα domain of the editing enzyme dsRNA adenosine deaminase binds left-handed Z-RNA as well as Z-DNA - Brown, Bernard A. (The National Academy of Sciences, 2000)
The Zα domain of human double-stranded RNA adenosine deaminase 1 binds specifically to left-handed Z-DNA and stabilizes the Z-conformation. Here we report spectroscopic and analytical results that demonstrate that Zα can also stabilize the left-handed Z-conformation in double-stranded RNA. Zα induces a slow transition from the right-handed A-conformation to the Z-form in duplex r(CG)(6), with an activation energy of 38 kcal mol(−1). We conclude that Z-RNA as well as Z-DNA can be accommodated in the tailored binding site of Zα. The specific binding of Z-RNA by Zα may be involved in targeting double-stranded RNA adenosine deaminase 1 for a role in hypermutation of RNA viruses.